The Influence of Self-Efficacy, Emotional Intelligence and Anxiety on the Level of Motivation When Competing in PPLPD Pencak Silat Athletes Musi Banyuasin Regency - Swidinata, Surya; Kristina, Putri Cicilia; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the effect of self-efficacy, emotional intelligence and anxiety on the level of motivation when competing in Pencak Silat PPLPD athletes in Musi Banyuasin Regency. This type of research is descriptive using a survey method. Data collection techniques using a questionnaire. The subjects of this study were 28 Pencak Silat PPLPD athletes in Musi Banyuasin Regency. Data analysis techniques use quantitative descriptive. The results showed that the self-efficacy level of Pencak Silat PPLPD athletes in Musi Banyuasin Regency was in the very high category of 50%, the level of emotional intelligence was in the high category of 54%, the level of anxiety was in the medium category of 68% which had an influence on athlete motivation. Pencak Silat PPLPD Musi Banyuasin Regency when competing with the level of motivation was in the very high category of 57%.